A cost-benefit analysis on an indicative valuation of the Arroceros Forest Park's ecosystem services on four development options - Achacoso, Inez Camille Marie P.; Navarra, Nappy T. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
Urban forests play an important role in the urban environment. They possess ecosystem services that contain benefits to improve the quality of life in the city. The Arroceros Forest Park is the only remaining forest park in Metro Manila and is faced with a threat of a development that would eradicate the forest park and be converted into a gymnasium. Given this, not only will trees be misplace to make way for the construction, it also imposes a lot of environmental challenges in the urban setting. With the rapid developments in Manila, how can these green spaces be valued and prioritized? The study intends to review the different ecosystem services provided by the Arroceros Forest Park, specifically carbon sequestration and recreational benefits. Four development scenarios were created to present other development opportunities in the park that would minimize the impact of development on the environment. An indicative valuation is conducted to provide monetary values to the ecosystem services these scenarios have. By using these values, a cost-benefit analysis is performed to determine the most viable development for the Arroceros Forest Park. The result of the analysis concludes that Scenario C, a landscape development that would maintain the existing trees in the site and introduce more recreational spaces for users to enjoy, is the most feasible development option for the Arroceros Forest Park.
Includes appendices
Best Thesis (Landscape Architecture) AY 2017-2018, 1st place
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Ecosystem services